CeO2-TiO2 for Photoreduction Of CO2 To Methanol Under Visible Light: Effect Of Ceria Loading - Hamidah, Abdullah; Nur Aminatulmimi, Ismail; Zahira, Yaakob; Khan, Maksudur R.; Syarifah, Abd Rahim (The Malaysian Analytical Sciences Society, 2017)
A visible light-driven photocatalyst, CeO2-TiO2 catalyst with different ceria loading was synthesized by impregnation method between TiO2 powder and cerium oxide nanoparticles slurry. The prepared catalyst samples were characterized by X-ray diffraction (XRD), surface area analysis, UV-vis absorption spectroscopy and photoluminescence spectroscopy (PL). The band gap of CeO2-TiO2 catalyst was found to be 2.15–2.4 eV. The band gap reduction clearly indicated the successful loading of CeO2 on TiO2. The photocatalytic activity was determined by measuring the photoreduction of CO2 to methanol in aqueous solution under visible light. The effect of cerium loading in the range of 1 to 5 wt% on the photocatalytic activity was studied and 2 wt% CeO2-TiO2 was found to exhibit the maximum photoactivity of 18.6 μmo l/g.catalyst after 6 hours irradiation. Results showed that the prepared photocatalyst is visible light active and may be used as effective catalyst in photoreduction of CO2 to methanol.